When Should a Black Box Be Transparent? When is a replacement not a replacement? - Neville-Neil, George V.; K. V. (Communications of the ACM, 2022)
The article presents a discussion about when a third party vendor's component is considered to be a drop-in replacement item for the original component, and it mentions supply chain problems, a computer application programming interface (API), and computer software malleability The need to ask for information from vendors in order to reduce risk is assessed, as well as replacement-related test plans, test output data, and computer hardware.